SUSCEPTIBILITY OF S.AUREUS TO METHYLENE BLUE HAEMATOPORPHYRIN, PHTALOCYANINES PHOTODYNAMIC EFFECTS - Tzvetelina Gueorgieva; Slavcho Dimitrov; Violeta Dogandhiyska; Vasil Kalchinov; Marieta Belcheva; Vanya Mantareva; Ivan Angelov; Veselin Kussovski (Peytchinski Publishing, 2010)
Introduction: Many of oral diseases are caused by microorganisms. The emergence of antibioticresistant strains, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecalis, stimulated a search for alternative treatments. Such an alternative method is photo-activated disinfection. The aim of this study is to compare the antimicrobial properties of four new photosensitizers - methylene blue, haematoporphyrin and new Ga, Zn- phtalocyanines after the laser radiation (630 nm) against Staphylococcus aureus . Materials and methods: For the study gram-positive Methicillin-resistant Staphylococcus aureus 1337 from collection of the Institute of Microbyology, Bulgarian Academy of Science is used. For PAD is used source of light which activates photosensitizer trough emission of visible light at a specific wavelength. Suspensions of Staphylococcus aureus was irradiated with diode laser (630 nm) in the presence of methylene blue, haematoporphyrin and new Ga, Zn- phtalocyanines. There were two control groups: samples that were only treated with dye and samples that were exposed neither to the laser light nor to dye. Results: Reduction in the viability of Staphylococcus aureus was achieved with some of the photosensitizers and light associations. Conclusions: Photoactivated disinfection appears as an effective method of Staphylococcus aureus inactivation.